The Managers' perception of UPV graduate applicant - Acevedo, Angela Socorro; Alcarde, Mark Anthony; Galuego, Ezekiel Paul.; Lim, Dyan Michelle (2004.)
This study aims to find out the different perceptions of managers on a UPV graduate applicant. The respondents of this study are managers and human resource supervisors of different private organizations in Iloilo City. 25 respondents were selected using the simple random sampling from the banking sector, hotels, malls aand department stores, restaurant and food chains, insurance corporations and other organizations. In obtaining data from the respondents, 35 questionnaires were distributed to the randomly selected organizations. The study inquired on the socio-economic profile of manager respondents to pin point the factors that has affected their perceptions of a UPV graduate applicant. The study shows that companies prefer applicants fromUPV because of the quality of their education and their attitude towards their work. But some organizations have also given importance to the skill of the applicant as a main factor when hiring new employees. some organizations, however, have opted not to choose applicants from UPV because of their questionable security of tenure and their high level of self-confidence as well as self-satisfaction which affects the relationship towards their co-workers.
Research Paper (Mgt 199 - Management Research) -- Iloilo City : University of the Philippines in the Visayas, College of Management, March 14, 2004.